2023
DOI: 10.3389/fvets.2023.1001621
|View full text |Cite
|
Sign up to set email alerts
|

Dietary spirulina supplementation modifies rumen development, fermentation and bacteria composition in Hu sheep when consuming high-fat dietary

Abstract: IntroductionThis study aims to investigate the long-term effects of spirulina supplementation in a high-fat diet (HFD) on rumen morphology, rumen fermentation, and the composition of rumen microbiota in lambs. Spirulina is a blue-green microalgae that has been shown to have high nutritional value for livestock.MethodsFifty-four lambs were randomly divided into three groups: a normal chow diet (NCD) group, a high-fat diet (HFD) group, and a high-fat diet supplemented with 3% spirulina (HFD+S) group. Rumen morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
1
2
0
Order By: Relevance
“…Spirulina supplementation raised VFA levels. Furthermore, VFA, the main product of rumen fermentation, has shown to have a wide range of impacts on ruminant physiology (Baxter et al, 2019;Wang et al, 2023). This study supports the findings of Christodoulou et al (2023), who evaluated the feeding Spirulina at the dosage of 15 g/ewe/day resulted in changes of rumen microorganisms population, and effect on the VFA in ruminal digest (Christodoulou et al, 2023).…”
Section: Liver Enzymes Activity Alanine Transaminase Enzyme Activity ...supporting
confidence: 81%
“…Spirulina supplementation raised VFA levels. Furthermore, VFA, the main product of rumen fermentation, has shown to have a wide range of impacts on ruminant physiology (Baxter et al, 2019;Wang et al, 2023). This study supports the findings of Christodoulou et al (2023), who evaluated the feeding Spirulina at the dosage of 15 g/ewe/day resulted in changes of rumen microorganisms population, and effect on the VFA in ruminal digest (Christodoulou et al, 2023).…”
Section: Liver Enzymes Activity Alanine Transaminase Enzyme Activity ...supporting
confidence: 81%
“…Previous studies have revealed that the rumen development process could be divided into three phases: non-rumination (0~3 weeks), transition (3~8 weeks), and rumination (8 weeks later) [27,56]. This was basically consistent with what we observed in the rumen of yaks, that is, there was no solid content in group 0 d, less forage and more milk in group 20 d, more forage and more milk in group 60 d, and only forage in group 15 m and group 3 y, indicating that yaks entered the transition stage of ruminant earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted on the administration of Spirulina microalgae (Athrospira sp.). For example, Wang et al (2023) examined increases in body score condition (BCS), body weight, and reproductive performance by supplementing Spirulina sp. Mansour and Zeitoun (2023) examined at growth performance, puberty, and blood metabolism in goats given Spirulina supplements; and Eldaim et al (2018) gave a combination of Spirulina sp.…”
Section: Introductionmentioning
confidence: 99%